2015
DOI: 10.1016/j.jcrysgro.2015.02.100
|View full text |Cite
|
Sign up to set email alerts
|

Growth temperature dependent critical thickness for phase separation in thick (~1 μm) In Ga1−N (x=0.2–0.4)

Abstract: This paper reports phase separation in thick (~1 µm) MOVPE In x Ga 1-x N (x = 0.2~0.4) films grown by MOVPE at 570~750˚C on AlN/Si(111), α-Al 2 O 3 (0001) and GaN/α-Al 2 O 3 (0001) substrates. Phase separation occurs when InGaN thickness exceeds a critical value. Critical thickness for phase separation is markedly increased with decreasing growth temperature. It is around 0.2 µm for a film grown at 750˚C, while it is more than 1 µmfor that grown at 570˚C. No substrate dependencies are found in critical thickne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Also, note that lower (≤600°C) temperature growth is the key to suppressing phase separation during the MOVPE growth of InN-rich thick InGaN films. 10) We previously proposed the use of platinum group metals as NH 3 decomposition catalysts for the MOVPE of InN 11) and GaN. 12) InN films with lower carrier density and higher electron mobility were obtained using such catalysts, 11) and the carbon contamination level in GaN was markedly reduced.…”
Section: Introductionmentioning
confidence: 99%
“…Also, note that lower (≤600°C) temperature growth is the key to suppressing phase separation during the MOVPE growth of InN-rich thick InGaN films. 10) We previously proposed the use of platinum group metals as NH 3 decomposition catalysts for the MOVPE of InN 11) and GaN. 12) InN films with lower carrier density and higher electron mobility were obtained using such catalysts, 11) and the carbon contamination level in GaN was markedly reduced.…”
Section: Introductionmentioning
confidence: 99%
“…This is due to the fact that Hall measurement data for InGaN grown on AlN/p-Si substrates are somewhat affected by the presence of the conductive Si substrate, in spite of the presence of the AlN interlayer (100 nm thick). It has been also confirmed that no difference in the phase separation behavior of MOVPE InGaN is found between AlN/p-Si and a-Al 2 O 3 (0001) substrates [11]. Figure 5 shows the annealing temperature T act dependence On the other hand, m is markedly decreased for T act > 700 8C, and reached 0.1-0.01 cm 2 Vs at T act ¼ 850 8C.…”
Section: Methodsmentioning
confidence: 52%
“…Critical thickness for phase separation is increased with decreasing growth temperature [11]. For example, a 1 mm-thick InGaN can be obtained at a growth temperature 600 8C or less, whereas a film as thin as 0.3 mm shows phase separation when it is grown at 750 8C.…”
mentioning
confidence: 99%
“…The dotted line, drawn between samples with and without phase separation, shows critical thicknesses for phase separation at different growth temperatures. 14) Critical thickness for phase separation in InGaN is markedly decreased with increasing growth temperature. Because phase separation seems to be caused by the solid-state diffusion of constitutional atoms and its rate seems to be governed by diffusion mobility of constitutional atoms, a smaller critical thickness at a higher temperature shows a larger diffusion mobility of constitutional atoms.…”
Section: Resultsmentioning
confidence: 99%